Tillage systems for the West African semiarid tropics - Hulugalle, N.R.; Maurya, P.R. (Elsevier, 1991)
The West African Semi-Arid Tropics (WASAT) is characterized by a monomodal rainfall pattern, and based on the amount of annual rainfall it can be divided into three ecologies: Sahel, Sudan and Northern Guinea savannahs. The major soil groups of the WASAT are Alfisols, Inceptisols and Entisols and Vertisols, with the former three predominating. The major soil constraints to crop growth are: soil compaction, low fertility, high temperature and low soil water retention, available water holding capacity and infiltration rate. Tillage in traditional farming systems is manual. However, mechanization of tillage operations has received emphasis in the recent past. The accelerated soil degradation which is a feature of mechanized-tillage systems under rainfed agriculture can be minimized with no tillage. However, lower yield have been reported to occur with no tillage. Some possible reasons are: the absence or low amounts of residue mulch, high soil compaction, the presence of harmful soil insects in crop residues, the creation of stable pores by tillage in soils of high organic matter, silt and fine sand contents. Unavailability of crop residues in a major impediment to the adoption of no tillage. The use of heavy and intensive mechanical tillage in irrigated agriculture leads to the formation of plow soles. Deep tillage such as subsoiling does not ensure the elimination of plow soles. While no tillage appears to hold promise for use in the irrigated agriculture of the WASAT much research remains to be done.